The cytosolic Arabidopsis thaliana cysteine desulfurase ABA3 delivers sulfur to the sulfurtransferase STR18 - Selles, Benjamin; Moseler, Anna; Caubrière, Damien; Sun, Shengkai; Ziesel, Morgane; Dhalleine, Tiphaine; Hériché, Mathilde; Wirtz, Markus; Rouhier, Nicolas; Couturier, Jérémy (The journal of biological chemistry, 2022)
The biosynthesis of many sulfur-containing molecules depends on cysteine as a sulfur source. Both the cysteine desulfurase (CD) and rhodanese (Rhd) domain-containing protein families participate in the trafficking of sulfur for various metabolic pathways in bacteria and human, but their connection is not yet described in plants. The existence of natural chimeric proteins containing both CD and Rhd domains in specific bacterial genera, however, suggests a general interaction between these proteins. We report here the biochemical relationships between two cytosolic proteins from Arabidopsis thaliana, a Rhd domain-containing protein, the sulfurtransferase 18 (STR18), and a CD isoform referred to as ABA3, and compare these biochemical features to those of a natural CD-Rhd fusion protein from the bacterium Pseudorhodoferax sp. We observed that the bacterial enzyme is bifunctional exhibiting both CD and STR activities using l-cysteine and thiosulfate as sulfur donors but preferentially using l-cysteine to catalyze transpersulfidation reactions. In vitro activity assays and mass spectrometry analyses revealed that STR18 stimulates the CD activity of ABA3 by reducing the intermediate persulfide on its catalytic cysteine, thereby accelerating the overall transfer reaction. We also show that both proteins interact in planta and form an efficient sulfur relay system, whereby STR18 catalyzes transpersulfidation reactions from ABA3 to the model acceptor protein roGFP2. In conclusion, the ABA3-STR18 couple likely represents an uncharacterized pathway of sulfur trafficking in the cytosol of plant cells, independent of ABA3 function in molybdenum cofactor maturation.
Available online 19 February 2022
Gesehen am 07.07.2022